The trouble begins at 8 : a life of Mark Twain in the wild, wild West - Fleischman, Sid, 1920-2010. (New York : Greenwillow Books, 2008)
A narrative account of the childhood and youth of nineteenth-century writer Mark Twain. Includes period engravings, newspaper cartoons, and black-and-white photographs.
The man who made frogs famous -- Eggs, three cents a dozen -- The gingerbread kid -- Upside down and backwards -- The riverboat rajah -- The cruel river -- Sam and the fortune teller -- Two weeks as a warrior -- The buffalo that climbed a tree -- Thieves, murderers, and desperados -- Gold, ten cents an acre -- Sam and the petrified man -- The duel at dawn -- Sam in the big city -- The slouching man -- The talking bluejay -- The water boy from Jackass Hill -- Goodbye, Sam; hello, Mark -- The sandwich chronicles -- The trouble begins at 8 -- The great holdup -- Twain attempts to behave -- Golden Gate, so long.
Includes bibliographical references and index.
School Library Journal starred.
Wilson's Children.
Wilson's Junior High School.
Booklist starred, June 2008.
Bulletin (Center for Children's books), July 2008.
Keywords: Twain, Mark, -- 1835-1910 -- Childhood and youth -- Juvenile literature; Twain, Mark, -- 1835-1910 -- Homes and haunts -- West (U.S.) -- Juvenile literature; Twain, Mark, -- 1835-1910.; Twain, Mark, -- 1835-1910.; Authors, American -- 19th century -- Biography -- Juvenile literature; Authors, American; American authors -- Biography